TEACHING OF REPRESENTATIVES OF WORLD LITERATURE AND THEIR WORKS IN CLASSROOM LESSONS OF THE PRIMARY CLASS - Abdug'affarova Mashhura (PEDAGOGS, 2025)
Abstract: In this article, theoretical information is given about the status of teaching representatives of world children's literature and their works in extracurricular reading classes of elementary school, its importance in the development of children's speech, and its role in the formation of children's reading culture.